Pemerihalan Naratif Riwayat Hidup Mustafa Iii (1775-1774) [an Analytical Narrative Of The Life History Of Mustafa Iii (1757–1774)] - Muhamad Hasanuddin Mohd Hatta; Ezad Azraai Jamsari; Anwar Muttaqin; Mohamad Zulfazdlee Abul HassanAshari; Ermy Azziaty Rozali; Ahmad Shukri Johara; Muhammad ZharifBaharudin; Adibah Sulaiman @ Mohamad (NUN Gemilang, 2025)
Indexed by MyCite